2021
DOI: 10.1037/ppm0000298
|View full text |Cite
|
Sign up to set email alerts
|

The effects of interaction fidelity on game experience in virtual reality.

Abstract: Natural user interfaces (NUIs) have been shown to significantly enhance video gaming experiences in some cases; however, questions have been raised about how effective NUIs are at increasing sense of presence, interactivity, realism, and enjoyment in games where actions taken with the controller do not synchronize well with the actions performed in game. In an effort to investigate these questions, several games were evaluated for interaction fidelity (IF): How closely in-game actions are matched by user input… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…However, this restriction especially of body movements was desired to interfere as little as possible with the EEG measurement. Yet, the participants were not completely passive in this setting: They were able to control their field of view either by head-motion (RL and VR) which offered high interaction fidelity between both conditions ( Shafer, 2021 ; see also, e.g., Riva, 2006 ; Cipresso et al, 2018 ; Kisker et al, 2021c ) or were mediated by keystrokes (PC). Moreover, they were surrounded by a photorealistic 3D environment in both former conditions, while the PC condition was limited to a large 2D screen.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, this restriction especially of body movements was desired to interfere as little as possible with the EEG measurement. Yet, the participants were not completely passive in this setting: They were able to control their field of view either by head-motion (RL and VR) which offered high interaction fidelity between both conditions ( Shafer, 2021 ; see also, e.g., Riva, 2006 ; Cipresso et al, 2018 ; Kisker et al, 2021c ) or were mediated by keystrokes (PC). Moreover, they were surrounded by a photorealistic 3D environment in both former conditions, while the PC condition was limited to a large 2D screen.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, they were surrounded by a photorealistic 3D environment in both former conditions, while the PC condition was limited to a large 2D screen. Considering that, involvement should definitely differ between the former two and the latter conditions as high interaction fidelity increases the presence, interactivity, and realism ( Shafer, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Technical advances in the development of virtual environments (VE) and virtual reality (VR) headsets and devices for the video games industry [46,47] or social media [48,49] have now made it possible to develop applications related to human-robot interaction. In particular, in mobile robot applications, some interesting works using VR can be found.…”
Section: Virtual Reality-based Interfacesmentioning
confidence: 99%
“…Against these backdrops, this study proposes one's FOP as a mediator between IGA interactivity and purchase intention. According to Shafer (2021), an individual's FOP is influenced by interactivity, and it can determine customers' response toward the brand/ product. Therefore, this study argues that IGA interactivity influences one's FOP which leads to favorable purchase intention.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, Vashisht's (2016) thought strikes that integrating brands in games might serve as an opportunity to gain customer attention (because of embedded brand messages) and to increase advertising effectiveness (Yoo and Eastin, 2016). Recent studies have identified that advergames are more effective as compared to traditional media channels (Shafer, 2021; Vashisht, 2021) because customers actively interact and engage with the embedded brands in advergames for a longer period (Vashisht et al , 2021), and higher brand engagement positively influences customers' purchase intention (Jiménez-Castillo and Sánchez-Fernández, 2019).…”
Section: Introductionmentioning
confidence: 99%